Application of Serpent 2 and MCNP6 to study different criticality configurations of a VVER-1000 mock-up. (August 2016) - Chersola, D.; Mazzini, G.; Košťál, M.; Miglierini, B.; Hrehor, M.; Lomonaco, G.; Borreani, W.; Ruščák, M.
Highlights: Serpent 2 and MCNP6 Monte Carlo codes applied to a mock-up of VVER reactor. Nuclear detectors evaluated in an experimental facility. Analysis of an experimental facility in different criticality configurations. Abstract: This paper shows some results obtained through simulating a VVER-1000 mock-up installed within the LR-0 research reactor in the Research Centre Řež (Czech Republic): the simulations have been performed by using the Serpent 2 and MCNP6 Monte Carlo codes. The mock-up is analysed in 6 different critical configurations, obtained with variation of coolant level and boron concentration. Some important nuclear parameters are evaluated in different positions of the mock-up, in order to know how the level of coolant influences the flux, the fission density, the reaction rate and the neutron spectrum changes, although the reactor remains with keff around 1.0 to less than 300 pcm of reactivity.